The Effects of The Covid-19 Pandemic on Exploitative and Explorative Strategies of Pharmaceutical Industries in Brazil - Neto, Macario Neri Ferreira; Forte, Sergio Henrique Arruda Cavalcante; Juliao, Flavio; Viana, Cristiane Maria Galvao (International Journal of Business, Economics and Management, 2021)
The survey assesses whether changes in highly competitive market environments have led pharmaceutical companies in Brazil to adjust their corporate strategies in order to maintain or expand their performance. The study is of a theoretical-empirical type, and supported by a regression model and content analysis. Data collection applied questionnaires and interviews with managers of the pharmaceutical industries in two moments. The questionnaire referred to previous information (year 2019) and during the Covid-19 pandemic (June and December 2020). The interviews sought answers about future perspectives. As main results, the correlations between Market Turbulence, Exploitation, Exploration, Ambidexterity and Performance were positively validated, with the exception between Market Turbulence and Exploitation in 2019 and between Market Turbulence and Exploitation and also Exploration in 2019 and 2020. It is clear that companies in the pharmaceutical industry in Brazil changed their strategies to maintain or expand their performance in the face of this uncertain scenario, keeping exploration at levels similar to the previous year, but seeking balance in terms of exploitation, in the pursuit of ambidexterity, optimizing advantages of both strategies, with the mitigation of risks inherent to a turbulent scenario.